Does a combination of physical training, specific exercises and pain education improve health-related quality of life in patients with chronic neck pain? A randomised control trial with a 4-month follow up. (December 2016) - Ris, I.; Søgaard, K.; Gram, B.; Agerbo, K.; Boyle, E.; Juul-Kristensen, B.
Abstract: Aim: To investigate the effect of combining pain education, specific exercises and graded physical activity training (exercise) compared with pain education alone (control) on physical health-related quality of life (HR-QoL) in chronic neck pain patients. Methods: A multicentre randomised controlled trial of 200 neck pain patients receiving pain education. The exercise group received additional exercises for neck/shoulder, balance and oculomotor function, plus graded physical activity training. Patient-reported outcome measures (Short Form-36 Physical and Mental component summary scores, EuroQol-5D, Beck Depression Inventory-II, Neck Disability Index, Pain Bothersomeness, Patient-Specific Functioning Scale, Tampa Scale of Kinesiophobia, Global Perceived Effect) and clinical tests (Aastrand Physical Fitness, cervical Range of Motion, Pressure Pain Threshold at infraspinatus, tibialis anterior and cervical spine, Cranio-cervical Flexion, Cervical Extension muscle function, and oculomotion) were recorded at baseline and after 4 months. Results: The exercise group showed statistically significant improvement in physical HR-QoL, mental HR-QoL, depression, cervical pressure pain threshold, cervical extension movement, muscle function, and oculomotion. Per protocol analyses confirmed these results with additional significant improvements in the exercise group compared with controls. Conclusions: This multimodal intervention may be an effective intervention for chronic neck pain patients. Trial registration: The trial was registered onwww.ClinicalTrials.gov NCT01431261 and at the Regional Scientific Ethics Committee of Southern Denmark S-20100069. Highlights: Physiotherapy for chronic neck pain patients is recommended. Effect of pain education vs. pain education, exercises, graded activity was studied. Outcomes were patient reported outcomes and clinical tests after 4 months. The training/exercise group improved superior on Health Related Quality of Life. Good adherence increased the effect of the intervention.